Peran Guru Pendidikan Jasmani dalam Meningkatkan Minat Belajar Renang Siswa di SDN 12 Konda - La Ode Ahmad Yusran (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine the role of Physical Education teachers in increasing students' interest in swimming at SDN 12 Konda. This research used a qualitative approach with descriptive methods. The subjects consisted of Physical Education teachers and fifth-grade students participating in swimming lessons. Data were collected through observation, semi-structured interviews, and documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The results indicate that Physical Education teachers actively and optimally carry out their role in increasing students' interest in swimming. The teacher's role is reflected as a motivator through encouragement, praise, and positive reinforcement, which can reduce students' fear of water. As a facilitator, the teacher prepares supporting facilities and uses simple aids and learning methods tailored to the students' abilities. The teacher's role as a guide is evident in the gradual implementation of swimming lessons and the provision of individual guidance to students experiencing difficulties. Furthermore, the teacher also serves as an evaluator by conducting ongoing evaluations of the learning process and outcomes, both in terms of skills and student learning interests. The conclusion of this study indicates that the role of Physical Education teachers is crucial in increasing students' interest in learning to swim. Therefore, teachers need to continuously develop their pedagogical and professional competencies so that swimming lessons can be effective, safe, and enjoyable.